(ARTICLE RETRACTED) The Political Challenge of Islamic Economic Development in The Jokowi’s Government, Indonesia - Dahlan, Ahmad (Ijtimā iyya Journal of Muslim Society Research, 2021)
(ARTICLE RETRACTED)